When “More” Seems Like Less: Differential Price Framing Increases the Choice Share of Higher-Priced Options - Allard, Thomas; Hardisty, David J.; Griffin, Dale (Journal of Marketing Research, 2019)
Four experiments supported by six supplemental studies show that premium but higher-priced products (e.g., direct flights, larger-capacity data storage devices) are more popular when the additional cost is made explicit using differential price framing (DPF; e.g., “for $20 more”) rather than being left implicit, as in standard inclusive price framing (IPF; e.g., “for $60 total”). The DPF effect is driven by pricing focalism: relative to IPF, DPF creates a focus on the price difference, which, because it is smaller than the total price, leads to lower perceived expensiveness and thus greater choice share for the premium option. This price framing effect is robust to displaying the total cost of the purchase, bad deals, and easy-to-compute price differences, and it appears to be uniquely effective in pricing contexts. However, DPF effects are reduced among consumers who adopt a slow and effortful decision process. These findings have implications for research on price partitioning, the design of effective pricing strategy, the sources of expensiveness perceptions in the marketplace, and consumer welfare.